PENGARUH PERSEPSI HARGA, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU MENGINAP DI GRAND BASKO HOTEL PADANG - Nurhaliza, Afdilla; Abrian, Youmil (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: This research is motivated by the rise and fall of guest occupancy rates at Grand Basko Hotel Padang every month and aims to see the effect of perceived price, brand image, service quality on guest satisfaction. The method in this study is a causal associative quantitative approach with survey mode. The population used in this study were individual guests who had stayed at the Grand Basko Hotel Padang, totaling 337 respondents. The sampling technique used is non-probability sampling, namely a purposive sampling technique that uses a sample determination with certain considerations or special selection. Sources of research data were obtained from primary data by distributing questionnaires via Google from to respondents, namely individual guests who had stayed overnight. Instrument trials were carried out by means of validity tests and reliability tests. To test requirements analysis using normality, multicollinearity, and heteroscedasticity tests in hypothesis testing using multiple linear analysis. The results of this study are that the price perception variable shows a pretty good category with a significant value of 0.481 > 0.05, the brand image variable shows a pretty good category, the service quality variable shows a pretty good category with a significant value of 0.00 > 0.05, then on the variable guest satisfaction shows a pretty good category. Keywords: Perceived Price, Brand Image, Service Quality, Guest Satisfaction